Electrical & electronic engineering : theory and application series 1 : ultrasonic and application - Mohd. Muji, Siti Zarina (Penerbit UTHM, 2015)
There are seven chapters in this book under computer engineering and robotics field. Among the topics that come from different disciplines of knowledge, including optimization algorithms, sensor technology, Arduino, FPGA, equipment, robots and systems on chip (SoC). All the topics discussed from basic to help readers understand easily. There are also included the source code for a particular topic, so it can motivate readers to study it in depth and can use the source code for further investigations.